Employability, proactiveness and workplace behaviors: is socioeconomic status a mediator? - Păunescu, Carmen; Acatrinei, Carmen; Argatu, Ruxandra; McGuire, Stephen J. J.; Zhang, Yang (Journal of Business Economics and Management, 2024)
The paper aims to examine individuals’ behavior at work and/or in college, by placing the focus on employability, proactiveness and socioeconomic status as predictors. The paper’s objectives are threefold: (1) to examine if there is a causal relationship between employability and proactive personality of individuals and their citizenship or deviant behavior at work and/or in college; (2) to understand the extent to which socioeconomic status influences individuals’ citizenship or deviant behavior at work and/or in college; and (3) to determine the mediation role of socioeconomic status in the causal relationship between employability and proactiveness and individuals’ behaviors. Linear regression models were employed to test the predictive power of the variables once a causal relationship had been confirmed. Mediation tests were used to quantify the extent to which a variable participated in known causal relationships. The research reports results based on data collected from 534 university business students in Romania. The results confirm that employability and proactiveness predict workplace behavior, and that socioeconomic status mediates this relationship.